A Human Rights Perspective on Palliative Care: Unraveling Disparities and Determinants Among Asian American Populations. Issue 3 (July 2020) - Mukherjea, Arnab; Ali, Shabana; Smith, Jason A.
Abstract : Purpose: Palliative care is regarded as fundamental to human dignity and falls under the definition of basic human rights. One considerable community of color whose needs are poorly understood consists of Asian Americans, including distinct priorities, expectations, and decision-making processes by diverse subgroups. The purpose of this work was to understand whether and to what extent unique considerations are understood among Asian American subgroups. Method: A scoping review was conducted among major scientific and academic databases. Broad search terms surrounding end-of-life care were combined with individual racial and ethnic identifiers encompassing Asian American subgroups. Results: Twenty-two articles met inclusion criteria and reflected diverse arrays of worldviews surrounding access to, utilization of, and desired outcomes from palliative care. Most articles focused on social orientations prioritizing family in disease disclosure and avenues of interventions sought with distinct patterns among subgroups. Discussion/Conclusion: A human rights framework emphasizing palliative and other end-of-life approaches to care may be inadequate to address unique considerations among diverse Asian American subgroups. Theorists and practitioners should incorporate practices of collectivist orientations and family contexts commonly found among these diverse communities.